Perception of social prosperity in indigenous tourism destinations in Mexico: The mediator effect of competitiveness of the destinations - Jorge Luis Ramos-García; Delfino Vargas-Chanes; Arcelia Toledo-López (Cogent Business & Management, 2023)
In this study, the relationship between community social capital and social prosperity is analysed, as well as the mediatory effect of competitiveness in indigenous tourism destinations from the perspective of the residents in indigenous communities. The sample was 103 people from 10 communities that are recognised as indigenous communities as affiliates of the Red Indígena de Turismo de México A.C. (RITA) (Indigenous Network of Tourism in Mexico). The analysis of the data and proof of hypothesis was carried out through partial least squares structural equation modelling (PLS-SEM). The discoveries show that the competitiveness of the destinations has a mediatory effect between the community social capital and the perception of social prosperity. It was found that the indigenous people perceive social prosperity through the competitiveness of the destination given that said competitiveness has various effects; more tourists have arrived at the destination, the tourist activities that benefit the local economy have been better managed, the creation of new businesses and jobs, entrepreneurship, investment in infrastructure, improvement in access to public services, and care for the natural resources of the communities. This competitiveness is directly influenced by the community social capital of the indigenous tourism destinations.
Keywords: 650; community social capital; indigenous tourism; social prosperity; structural equation modelling; tourism destination competitiveness